2019
DOI: 10.1249/mss.0000000000001898
|View full text |Cite
|
Sign up to set email alerts
|

Novel Noninvasive Assessment of Microvascular Structure and Function in Humans

Abstract: Introduction Optical coherence tomography (OCT) is a novel high-resolution imaging technique capable of visualizing in vivo structures at a resolution of ~10 μm. We have developed specialized OCT-based approaches that quantify diameter, speed, and flow rate in human cutaneous microvessels. In this study, we hypothesized that OCT-based microvascular assessments would possess comparable levels of reliability when compared with those derived using conventional laser Doppler flowmetry (LDF). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“… 31 32 In this study we chose a modified local heating protocol which aimed to induce maximal vasodilation and so assess functional and structural aspects of microvascular dilation. 20 The impaired heating responses we observed in the DFU and DNU groups may be due to loss of neurogenic vasodilation and/or reduced synthesis of NO or other local factors. We think it will be possible in future studies, using a combination of OCT assessment and simultaneous microdialysis delivery of specific pathway antagonists, 33–35 to pharmacodissect individual pathways responsible for the regulation of cutaneous microvascular dysfunction/function in health and disease.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“… 31 32 In this study we chose a modified local heating protocol which aimed to induce maximal vasodilation and so assess functional and structural aspects of microvascular dilation. 20 The impaired heating responses we observed in the DFU and DNU groups may be due to loss of neurogenic vasodilation and/or reduced synthesis of NO or other local factors. We think it will be possible in future studies, using a combination of OCT assessment and simultaneous microdialysis delivery of specific pathway antagonists, 33–35 to pharmacodissect individual pathways responsible for the regulation of cutaneous microvascular dysfunction/function in health and disease.…”
Section: Discussionmentioning
confidence: 78%
“…Further details of this image acquisition and analysis are described elsewhere. 20 In brief, the characteristics of the speckle noise are related to blood flow speed, with faster blood flow giving rise to more rapid fluctuations in the speckle noise. Speckle indicating blood vessels is automatically delineated from the surrounding static tissue using standard imaging processing techniques, with the speckle fluctuations providing an estimate of flow speed at each point.…”
Section: Optical Coherence Tomographymentioning
confidence: 99%
See 1 more Smart Citation
“…The utility of OCTA for measuring the cutaneous microvasculature in response to a local heating protocol was recently demonstrated for the first time by Smith et al 24 The researchers imaged the ventral forearm of participants with OCTA while applying heat with a commercially available skin heating probe. While their study did well to introduce the concept of using OCTA with local heating for exercise physiology research, we believe the methods demonstrated in the current study offer several improvements that may help to advance the technique even further.…”
Section: Discussionmentioning
confidence: 99%
“…Similar, to laser perfusion imaging, the speckle pattern changes with movement of red blood cells compared to stationary tissue, which allows an estimate of the rate of blood flow. In recent studies from the same laboratory, OCT of the skin in the lower forearm was imaged alongside laser Doppler flowmetry during a 30 min bout of local heating to cause increases in skin blood flow (Carter et al 2016, Smith et al 2019. These studies uniquely demonstrated that the OCT technique can provide in-depth insight into the morphological and functional changes in skin vessels.…”
Section: Optical Coherence Tomographymentioning
confidence: 99%